2021
DOI: 10.1186/s12870-021-03131-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis reveals sesquiterpenoid biosynthesis among 1-, 2- and 3-year old Atractylodes chinensis

Abstract: Background Atractylodes chinensis (DC.) Koidz is a well-known medicinal plant containing the major bioactive compound, atractylodin, a sesquiterpenoid. High-performance liquid chromatography (HPLC) analysis demonstrated that atractylodin was most abundant in 3-year old A. chinensis rhizome, compared with those from 1- and 2-year old rhizomes, however, the molecular mechanisms underlying accumulation of atractylodin in rhizomes are poorly understood. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This phenomenon also occurred in Atractylodes atractylodes . By comparing A. atractylodes with different growth years, suggesting that the productivity of secondary metabolism of A. atractylodes increased with cultivation years, possibly because it was used to resist the pressure in old plants [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon also occurred in Atractylodes atractylodes . By comparing A. atractylodes with different growth years, suggesting that the productivity of secondary metabolism of A. atractylodes increased with cultivation years, possibly because it was used to resist the pressure in old plants [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the MCL survival differences between two patient groups dichotomized based on the expression of transcripts or immunocyte ratios was evaluated by calculating p values based on the log-rank test [ 48 ]. To evaluate the consistency between expression values obtained with whole transcriptome sequencing and qRT-PCR for selected transcripts, the p values were calculated via Pearson correlation testing for paired expressions [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…RNA extraction and sequencing were performed as described by Zhao et al (2021) [36]. RNA of A. chinensis was extracted using TRIzol Reagent (Invitrogen).…”
Section: Rna Sequencing and Core Ssr Marker Screeningmentioning
confidence: 99%
“…Transcriptome data of A. chinensis were acquired based on the Illumina Hiseq Xten PE150 platform, by Novogene Co. (Beijing, China). All SSR primers used in this study were designed from the transcriptomic database as reported by Zhao et al 2021 [36], and they are available in the SRA (BioProject ID PRJNA698794, https:// www. ncbi.…”
Section: Rna Sequencing and Core Ssr Marker Screeningmentioning
confidence: 99%